AMELIORATIVE POTENTIAL OF GLYCOSMIS PENTAPHYLLA (RETZ.) DC IN INDUCED ARSENICOSIS IN RATS - AMARTYA DE,; S.K. BANDYOPADHYAY,; T.K. MANDAL,; A.K DAS,; A. MISHRA, (International Journal of Pharma and Bio Sciences, 2016)
Arsenic poisoning is one of the major causes of chronic human illness and mortality in Bengal Delta plain with limited treatment options.The present study was conducted to evaluate the ameliorating effect of Glycosmis pentaphylla (Rutaceae) leaf extract against sodium arsenite (NaAsO2) induced toxicity. Forty eight adult albino rats were divided into four groups viz.,G0,G1,G2 and G3.Sodium arsenite was administered @ 4mg/kg daily in drinking water in groups G1, G2 and G3 for 90 days; the control group(G0) received water for 120 days.The G1 group of animals received water, instead of arsenic during 91-120 days , while rats of group G2 and G3 were orally treated with plant leaf extract at 320 mg/kg (1/10th LD50) and 160 mg/kg (1/20th LD50) respectively daily during the period. Analysis of arsenic concentrations in tissue samples,hair and faeces showed that treatment with G. pentaphylla leaf extract significantly (p<0.05) reduced arsenic accumulation in tissues, hair and in faeces. A significantly (p<0.05) higher organo-arsenic fraction and lower arsenite and arsenate fraction was also observed in G. pentaphylla leaf extract treated group(G2 &G3). The study showed that oral treatment with G.pentaphylla leaf extract could ameliorate induced arsenicosis.